Physico-mechanical properties of Sesenduk treated with direct contact method - Yunus, Mohd Hafiz (2017)
Nowadays, wood industries focus more on high quality wood which most of them are slow-growing trees which cause high pressure to the forest area. This study is carried out to improve the quality of Sesenduk which is fast-growing trees so that it can be used widely in wood industry and reduce pressure to the forest. Heat treatment known as direct contact method is performed on Sesenduk wood samples which use variation wood thickness, time and temperature of treatment. Samples of Sesenduk wood (80 mm × 320 mm) with the thickness of 1 cm, 1.5 cm and 2 cm were heat-treated at 160ºC, 180ºC and 200ºC with 15 min, 30 min and 45 min. For the result, water absorption, volumetric change, MOR, MOE and colour change are tested and observed. It shows that untreated samples have higher water absorption and volumetric change than treated samples which means that it is less durable and prone to fungi attack. Untreated samples also have no colour change compared to treated sample that have darker colour which indicates higher strength. MOR and MOE of treated samples are higher than untreated samples as heat treatment improves its physical and mechanical properties. Therefore, it can be concluded that direct contact method has improved Sesenduk quality.